Effects of Different Working Modes of Ultrasound on Structural Characteristics of Zein and ACE Inhibitory Activity of Hydrolysates - Xiaofeng Ren; Xi Zhang; Qiufang Liang; Ting Hou; Huiji Zhou (Journal of Food Quality)
Ultrasound was used as a new technology to pretreat protein prior to proteolysis to improve enzymolysis efficiency. The effects of different working modes of ultrasound on the angiotensin I-converting enzyme (ACE) inhibitory activity of zein hydrolysates and the structural characteristics of zein were investigated. The solubility, surface hydrophobicity (H0), ultraviolet-visible (UV-Vis) spectra, intrinsic fluorescence spectra, and circular dichroism (CD) spectra of zein pretreated with ultrasound were determined. All ultrasound pretreatments significantly improved the ACE inhibitory activity of zein hydrolysates (p<0.05). The highest ACE inhibitory activity, representing an increase of 99.21% over the control, was obtained with dual sweeping frequency ultrasound of 33±2 and 68±2 kHz. The effects of single sweeping frequency and dual fixed frequency ultrasound were stronger than those of single fixed frequency ultrasound for improving the ACE inhibitory activity of zein. Structural changes in zein were induced by ultrasound, as confirmed by changes in the solubility, H0, UV-Vis spectra, intrinsic fluorescence spectra, and CD spectra of zein, and these were consistent with the corresponding ACE inhibitory activities of zein hydrolysates. Thus, ultrasound working mode and frequency have significant effects on the structure of zein and the ACE inhibitory activity of zein hydrolysates.